How Public Procurement Policies Influence Sustainable Development Goals in Developing Countries: A Case Study in Vietnam - Van, Tuan Vu; Quang, Tuyen Nguyen (Lentera Hukum, 2025)
This research explores the role of public procurement in promoting sustainable development in Vietnam and examines how procurement policies align with the United Nations' Sustainable Development Goals (SDGs). As public procurement is a significant tool for achieving sustainable development, this study investigates the effectiveness of Vietnam's Law on Bidding, No. 22/2023/QH15, in integrating sustainability into public procurement practices. The study employs a qualitative case study method, utilizing primary data from document analysis, interviews with key procurement sector stakeholders, and secondary data from existing literature and governmental reports. The results indicate that although Vietnam has made progress in fostering green public and social procurement, the legal framework remains fragmented, with limited integration of comprehensive sustainability criteria across all procurement sectors. Challenges such as limited institutional capacity, market unpreparedness, financial constraints, and corruption continue to impede the effective implementation of sustainable procurement. In comparison with other developing countries like South Africa, India, and Brazil, Vietnam's approach is still in its early stages of development. The study concludes that while Vietnamese public procurement policies have the potential to generate greater sustainability, they require stronger regulations, enhanced institutional capacity, and greater market support. Strengthening the link between procurement and the SDGs is essential for achieving Vietnam’s long-term environmental, social, and economic sustainability goals.Keywords: Economic growth, Government spending, Procurement regulations, Procurement system, Public procurement.